Agripreneurs and their Opinion on Agri-Clinics and Agri-Business Centres Scheme - L.M. Ahire,; B.S. Sontakki,; P. Punna Rao, (Journal of Agricultural Extension Management, 2025)
Ensuring a competitive agricultural economy is critical for reducing poverty, enabling food, nutrition and livelihood security, and sustainable natural resource management. Even in this high-tech era, farming happens to be the primary livelihood support system for nearly 60% of our populace. Agriculture has already reached the limits of land and water, thus future increase in food production must exploit biological yields on existing land (World Bank, 1997). Hence, these challenges put tremendous pressure on agriculture to change from the way it used to be practiced earlier and even today. Agriculture of the next generation has to go beyond mere food production to be a propellant of economic development by being sustainable, environment friendly and market oriented